Youth Participation in Management of Deli Watershed (DAS Deli) in Medan - Hutasuhut, Ikhwan Kurnia; Sihombing, Marlon; Maas, Linda Trimurni (TALENTA Publisher, Universitas Sumatera Utara, 2022)
The current condition of the Deli Watershed (Daerah Aliran Sungai/DAS Deli) is in an appalling condition. This is indicated by several indicators experienced by the Deli Watershed, such as the decreasing amount of forests, polluted river water, slums along the river banks, silting of rivers, garbage dumped into rivers, so that all such conditions result in frequent floods in the City Field. This has become the author's interest to conduct a study entitled